POSTOPERATIVE RECOVERY OF SPYROID TIBIA FRACTURE - Silviu Gabriel CIOROIU (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics, 2020)
This paper is a topical issue among people diagnosed with spiral fracture third diaphyseal tibia, because following the survey conducted by the College of Physiokinetotherapists in Romania over 50% of athletes licensed to sports clubs are suffering from pathologies in the lower limbs, 20% of these at the tibia. In this paper are found some methods and ways of early and methodical application of kintetotherapy means and processes through which to restore as much as possible the functionality or loss of the patient diagnosed with spiral fracture middle third diaphyseal tibia. This paper aims to demonstrate that the proposed physiotherapy model helps to improve the functional capacity and quality of life in people with spiral fracture average third diaphyseal tibia.